Young swimmers’ kinematic and hydrodynamic detraining between a two seasons’ break - Costa, M.J. (2018)
Young swimmers usually have sever-al weeks of school break in the sum-mer. During such period no swim training is conducted until the begin-ning of the next season. According to training principles, the prolonged absence of a regular ex-ternal load may decrease the form status built up in a previous training period. Since the major focus of swim training in children is their technical enhancement, it is ex-pected that some adaptations will occur namely in kinematics and hy-drodynamic outcomes.